Impact of primary disease on outcome after allogeneic stem cell transplantation for transformed secondary acute leukaemia - Kröger, Nicolaus; Schönland, Stefan (British journal of haematology, 2019)
Myelodysplastic syndromes (MDS), myeloproliferative neoplasms (MPN) and chronic myelomonocytic leukaemia (CMML) can progress to secondary acute myeloid leukaemia (sAML). We compared the outcome of 4214 sAML patients who received allogeneic haematopoietic stem cell transplantation (allo-HSCT) from an unrelated (62%) or human leucocyte antigen (HLA)-identical sibling donor (38%) according the underlying disease: MDS (n = 3541), CMML (n = 251) or MPN (n = 422). After a median follow up of 46·5 months, the estimated 3-year progression-free (PFS) and overall survival (OS) for the entire group was 36% (34-37%) and 41% (40-43%), respectively. The cumulative incidence of relapse and non-relapse mortality (NRM) was 37% (35-39%) and 27% (26-29%), respectively. In a multivariable analysis for OS, besides age (P < 0·001), unrelated donor (P = 0·011), cytomegalovirus ± constellation (P = 0·007), Karnofsky index ≤ 80 (P < 0·001), remission status (P < 0·001), peripheral blood as stem cell source (P = 0·009), sAML from MPN (P = 0·003) remained a significant factor in comparison to sAML from MDS, while worse outcome of sAML from CMML did not reach statistical significance (P = 0·06). This large registry study demonstrates a major impact of the underlying disease on outcome of sAML after allo-HSCT.